Dietrich von Hildebrand’s Criticism of Amoral Sex Education - Puolimatka, Tapio (Acta Paedagogica Vilnensia, 2019)
This article analyzes Dietrich von Hildebrand’s criticism of amoral sex education, which he regards as misleading and anti-educational in many crucial respects. Its content is misleading, because it separates human sexuality from its inherent connection with married love and thereby fails to do justice to the personal and intimate nature of sexuality. Its reductive and neutralizing approach not only fails to develop young people’s capacity for the transcendence implicit in moral agency, it also fails to provide the preconditions for the development of their autheantic subjectivity. Instead of fostering objectivity, critical thinking and autonomy, amoral sex education promotes a normatively closed educational environment that fails to unfold young people’s potential for value-response and to contribute to the fulfilling of their human potential in general.